SISTEM MONITORING DAN KEAMANAN PINTU BERBASIS SMS VIA ARDUINO UNO - Mintorogo, Dwi Anggadi; Wiranata, Andi (Sekolah Tinggi Teknologi 10 Nopember, 2018)
Currently the need for security systems is increasing rapidly. The need is based on the number of theft cases, especially in areas that are less rapid in handling when theft occurs. Therefore, the purpose of this research is to design and build the door security system with limit switch sensors and SMS notification based on microcontroller which is expected to be able to solve the problem.                 To achieve this goal, Arduino IDE software is the software used to program the microcontroller on the security system. The hardware used is electronics components, namely Arduino Uno board, Sensor Limit Switch, Buzzer, LCD, Relay Module, GSM Module, and Mobile.                 Trials performed on this security system include: First, the testing function of the tool used. Second, Testing the maximum distance of the GSM module connection signal between the system keaamanan with Mobile. Third, Testing the time required for sending SMS up to the destination number.                 The test results are as follows: Limit Switch sensors can detect movement and function properly. The maximum distance from the GSM module connection signal on the security system is dependent on the sim card in use. The sending time of SMS notification until received by destination number is 2 seconds on good signal (5 bars), 5 seconds on medium signal (3 bars), and 8 seconds on bad signal (1 bar).